SOCIAL PHENOMENA “HALLYU WAVE” AMONG TEENAGERS IN RELATION TO LIFESTYLE PATTERNS - Eldi Mulyana; Nurfirmansyah Putri, Alsakinah; Nopharipaldi Rohman, Slamet (Institut Pendidikan Indonesia, 2025)
This research is motivated by the development of the current era of globalization, cultural differences are not an obstacle for someone to learn and know other cultures. This is proof that changes in globalization have changed the mindset and lifestyle of humans to become more modern and open to new cultures. Studying other cultures can be done in various ways, especially now which is the era of globalization and the virtual century where social reality develops on a global scale, especially as a result of advances in information technology. The purpose of this research is to identify the hallyu phenomenon through Korean dramas becoming very popular on Indonesian private television channels (TV). The research method used is qualitative with a case study approach. Data collection techniques in this study used observation, interviews and documentation. The results of this study indicate that the Hallyu Wave is a phenomenon that spreads popular culture from South Korea in various parts of the world. This Hallyu Wave cultural product includes: Drama (K-Drama), Pop Music (K-Pop), Fashion (K-Style). Utilizing technological advances in the form of the internet, parties involved in the popular culture industry also carry out a communication process with the aim of publication, promotion and persuasion to their fans through social media, namely with a virtual communication model.